VISUALISASI DEWI PERTIWI DALAM FOTOGRAFI EKSPRESI - Saputra, Kadek Indra Dwi; Raharjo, Anis; Bratayadnya, Putu Agus (Lp2mpp Isi Denpasar - Ps. Fotografi, 2021)
Environmental problems can result in the destruction of valuable nature such as forests, rivers, beaches and others, besides that environmental problem can also damage biodiversity which is very important for humans. Mother Earth as a picture of the Earth that is fertile in supporting the living things in it. To convey the meaning contained in the visualization work of Dewi Pertiwi, the creator conveys the meaning contained in the work of Dewi Pertiwi in expression photography, so that it can be understood by the general public. In the creation of this work the creator used digital imaging techniques. The creator uses the exploratory method and the observation method. In translating the Visualization of Dewi Pertiwi into visual works, the creator uses a semiotic theory which not only examines the denotative level to the connotative level, in addition to building the aesthetic value in this work the creator uses the aesthetic theory of photography. In the preparation of the work also pay attention to the visual elements. The visual elements in this work show more natural damage than the 4 elements in Panca Maha Butha, namely, fire, earth, water, air, accompanied by colors, textures and lines that are set by the creator into image processing. In addition to these elements, this work also prioritizes composition, balance, and complexity in order to achieve a unity in realizing the Visualization of the Goddess of Mother Nature in Expression Photography. The message conveyed in this work is that one day photographic works can be used as a reflection of what is happening in nature today, including as a form of awareness, reminder and the importance of protecting nature. In making each work, it must have a meaning and beauty value in each of his works, so that photography can be accepted more widely by the community. Keywords: Visualization, Dewi Pertiwi, Expression Photography